Different extra-coronal restoration options of hemisected teeth on structurally compromised mandibular molar: Report of two cases - Mohamed Khazin, Sobrina; Omar, Siti Hajar (IIUM Journal of Orofacial and Health Sciences, 2023)
Structurally compromised teeth tend to be extracted due to its their poor prognosis, however, hemisection may serve as an alternative option in selected cases. This case report is aimed to discuss two cases of hemisected mandibular molars with two different approaches for post-hemisection restoration. Case 1 presents with terminal tooth 37 diagnosed with a cracked tooth involving severe bone loss on the mesial root. The tooth was hemisected and restored with a mesially cantilevered full ceramic crown. Case 2 presents with root caries on an endodontically treated tooth 46 on a patient with bruxism, with an inadequate ferrule on the distal segment. The tooth was hemisected utilizing the socket preservation technique, and the tooth was restored with a conventional fixed-fixed bridge with a second abutment on tooth 47.